Everyday encounters with difference in urban parks: forging 'openness to otherness' in segmenting cities. Issue 4 (December 2019) - Barker, Anna; Crawford, Adam; Booth, Nathan; Churchill, David
Abstract: In a context of hyper-diversity and social polarisation, it has been suggested that public parks constitute crucial arenas in which to safeguard deliberative democracy and foster social relations that bind loosely connected strangers. Drawing on empirical research, we offer a more circumspect and nuanced understanding of the – nonetheless vital – role that parks can play in fostering civic norms that support the capacity for living with difference. As 'spaces apart', parks have distinctive atmospheres that afford opportunities for convivial encounters in which 'indifference to difference' underpins 'openness to otherness'. As places in which difference is rendered routine and unremarkable, the potency of parks for social cohesion derives from fleeting and unanticipated interactions and the weak ties they promote, rather than strong bonds of community that tend to solidify lines of cultural differentiation. Both by design and unintentionally, regulation and law can serve to foster or constrain the conditions that sustain conviviality.